2017
DOI: 10.18203/2349-3291.ijcp20171716
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal seizures and outcome in a NICU of a tertiary care hospital of Andhra Pradesh-an two year study

Abstract: Background: Seizures are the most frequent clinical manifestation of central nervous system dysfunction in the newborn with the incidence varying from 1-5%. Neonatal seizures often signal an underlying ominous neurological condition, most commonly hypoxia-ischemia, and others include stroke, intraventricular hemorrhage or intraparenchymal hemorrhage, meningitis, sepsis, and metabolic disorders. Neonatal seizures can permanently disrupt neuronal development, induce synaptic reorganization, alter plasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…These findings were consistent with the previous reports (Alcover-Bloch et al 2004;Ehrenstein et al 2007;Glass et al 2009). Moreover, the lower birth weight was a great risk factor for neonatal seizures (Lanska et al 1995;Nagaram et al 2017). Most of our neonates had seizures during the first week of life, consistent with the previous report (Galanopoulou 2015).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings were consistent with the previous reports (Alcover-Bloch et al 2004;Ehrenstein et al 2007;Glass et al 2009). Moreover, the lower birth weight was a great risk factor for neonatal seizures (Lanska et al 1995;Nagaram et al 2017). Most of our neonates had seizures during the first week of life, consistent with the previous report (Galanopoulou 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Infection was a second risk factor (37.93%). Many previous reports indicated that infection has an important impact on survival and neurodevelopmental consequences (Göpel et al 2006;Shah et al 2008), particularly sepsis and meningitis (de Jonge et al 2010), while other studies regarded metabolic disturbances as a second cause of neonatal seizures (Tekgul et al 2006;Nagaram et al 2017). The higher incidence of infection in our study may be due to poor antenatal care with resultant obstetrical problems, such as maternal prolonged rupture of membranes, dirty delivery settings, and missed management of other maternal conditions, which were previously mentioned (Göpel et al 2006;de Jonge et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations